Odpowiedzi

2010-04-11T23:24:03+02:00
P(x)=3xdo3-2x+b i H(x)=3xdo3-ax+3bx + 5

3x³ - 2x + b = 3x ³ -ax +3bx + 5

b = 5
-2x = -ax + 3bx
-2x = -ax + 15x

15 - a = -2
17 = a
2010-04-11T23:24:08+02:00
Dobierz liczby a i b aby wielomiany P(x)=3xdo3-2x+b i H(x)=3xdo3-ax+3bx + 5 były równe

P(x)=3xdo3-2x+b
H(x)=3xdo3-ax+3bx + 5 =3xdo3+x(-a+3b) + 5
-2=-a+3b→→a=3b+2
b =5
a=17
1 5 1
2010-04-11T23:26:25+02:00
3x³ - 2x +b = 3x³ - ax + 3bx + 5
-2x + b = (-a +3b)x + 5

Zapisujemy w układ równań:
-2 = -a + 3b
b = 5

-2 = -a +15
-17 = -a
a = 17
1 5 1